2021
DOI: 10.1186/s44149-021-00020-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of SARS-CoV-2 hosts among Brazilian mammals and new coronavirus transmission chain using evolutionary bioinformatics

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) and SARS-CoV-2 are thought to transmit to humans via wild mammals, especially bats. However, evidence for direct bat-to-human transmission is lacking. Involvement of intermediate hosts is considered a reason for SARS-CoV-2 transmission to humans and emergence of outbreak. Large biodiversity is found in tropical territories, such as Brazil. On the similar line, this study aimed to predict potential coronavirus hosts among Brazilian wild mammals based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Deer have a high population density and are kept as livestock [33]. Their ecological interactions place these animals at an important position in the SARS-CoV-2 transmission chain [34]. Interestingly, the present study showed that deer and bovids share identical ACE2 key residues (Fig.…”
Section: Vol 10 Nomentioning
confidence: 51%
“…Deer have a high population density and are kept as livestock [33]. Their ecological interactions place these animals at an important position in the SARS-CoV-2 transmission chain [34]. Interestingly, the present study showed that deer and bovids share identical ACE2 key residues (Fig.…”
Section: Vol 10 Nomentioning
confidence: 51%